Renal carcinoma with recurrent urinary infection in a young patient - Vasquez-Sullca, Roy R. (2019)
Renal cancer is a neoplasm with an incidence rate of 4,4% per 100 000 inhabitants worldwide; renal cell carcinoma accounts for 90% of malignant renal tumors. Recurrent urinary infections have a prevalence of 19% and constitute infections of at least two episodes in six months, or at least three episodes in a year. We present the case of a 25-year-old female patient who presented with recurrent urinary tract infections and who had a left renal tumor in a tomographic study. A radical nephrectomy was performed, whose surgical specimen confirmed pathological diagnosis of clear cell renal carcinoma. In young patients, renal carcinoma is an even more rare tumor, representing 8,7% of all patients diagnosed with renal cancer. Clinical suspicion of young women with infections should be promoted in the clinic recurrent urinary traumas requesting imaging tests, in order to guarantee an early diagnosis and adequate treatment if it were a renal tumor.